2018
DOI: 10.18632/oncotarget.24682
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 inhibition enhances platinum efficiency in ovarian cancer

Abstract: Chemotherapeutic resistance evolves in about 70 % of ovarian cancer patients and is a major cause of death in this tumor entity. Novel approaches to overcome these therapeutic limitations are therefore highly warranted. A disintegrin and metalloprotease 17 (ADAM17) is highly expressed in ovarian cancer and required for releasing epidermal growth factor receptor (EGFR) ligands like amphiregulin (AREG). This factor has recently been detected in ascites of advanced stage ovarian cancer patients. However, it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…In ovarian cancer cells, miRNA-34c-5p has been shown to directly 31 Similarly, ADAM17 (a disintegrin and metalloprotease 17) belongs to a kind of metalloprotease that can increase the shedding of AR, leading to ovarian cancer cells resistant to cisplatin treatment. 58 In the present study, we found that AR can promote cell mobility and increase Dox resistance in human chondrosarcoma cells.…”
Section: Discussionsupporting
confidence: 55%
“…In ovarian cancer cells, miRNA-34c-5p has been shown to directly 31 Similarly, ADAM17 (a disintegrin and metalloprotease 17) belongs to a kind of metalloprotease that can increase the shedding of AR, leading to ovarian cancer cells resistant to cisplatin treatment. 58 In the present study, we found that AR can promote cell mobility and increase Dox resistance in human chondrosarcoma cells.…”
Section: Discussionsupporting
confidence: 55%
“…ADAM17 is highly expressed in ovarian cancer cells. When ADAM17 was inhibited in ovarian cancer cell lines using either anti-ADAM17 antibody D1 or GW280264X, the cancer cells were sensitised to cisplatin-induced apoptosis, therefore significantly reducing cell viability [ 68 ].…”
Section: Adam17 Inhibitorsmentioning
confidence: 99%
“…Along this line, EMT has been suggested to be a prerequisite for muscle invasion/metastasis in bladder cancer [ 33 ], although the role of ADAMs in BCG-refractory bladder cancer has not been addressed in this study. Additionally, ADAM17 was shown to be enhanced by platinum-based chemotherapy and caused EGFR transactivation by stimulating AREG release [ 34 ]. In this context, ADAM17 inhibition sensitized cancer cells to cisplatin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%